Pembangunan Sistem Pengelolaan Pendistribusian Dana Bantuan Sekolah (Studi Kasus: Dinas Pendidikan Dan Kebudayaan Kota Serang) - Birald Muhammad Dayan; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Education quality is something that must be considered in the world of education, to improve the quality of education, all education units must have facilities and infrastructure in according to the standards. In schools in Serang city, there are problems regarding facilities and infrastructure, namely in the management of funds for school facilities and infrastructure. The first problem is that some schools find it difficult to submit school operational aid funds because the process is long and complicated. The second problem is that some schools also find it difficult to submit proposals for submitting funds for school facilities and infrastructure due to the distance of the school too far from the Serang City Department of Education. The third problem is the inaccurate flow of distribution funds, there are still many schools that must be immediately assisted but not covered all because the submission of school aid funds is given to schools that submit school facilities and infrastructure grants first, not schools whose conditions need help first. To solve these problems, research is carried out which is intended to build a system that is able to facilitate the submission of school facilities and infrastructure assistance and can prioritize schools that must be assisted in advance. This system is expected to be able to overcome existing problems and help improve the work efficiency of the Serang City Department of Education. This system has passed unit testing using whitebox testing, validation testing using blackbox testing which results in a 100% valid value, and compatibility testing where the results of the system can run on 8 different browsers.